Chaperonin-Containing TCP1 Subunit 6A Is a Prognostic Potential Biomarker That Correlates With the Presence of Immune Infiltrates in Colorectal Cancer - Sun, Hui; Wang, Yan; Jing, Hao-Yu; Yang, Xin-Yu; Shi, Xin-Xiu; Zhang, Jia-Hui; Yu, Yuan-Xiu; Gao, Li; Wang, Xin-Yue; Li, Wan-Hong; Yu, Lei (Frontiers in Genetics, 2021)
Aims: Chaperonin‑containing TCP1 subunit (CCT) 6A is an oncogenic 6th subunit of the CCT family. Nevertheless, not much is documented regarding its function in colorectal cancer (COAD). This investigation seeks to explore the role of CCT6A in the prognosis of COAD. Main methods: Sequencing data from the Gene Expression Omnibus (GEO) and Cancer Genome Atlas database (TCGA) were employed to analyze the expression of CCT6A and its involvement in various regulatory networks behind COAD. Oncomine and Gene Expression Profiling Interactive Analysis (GEPIA) analyzed Levels of expression and survival rates, while GEPIA was used to uncover further the functional networks that involved CCT6A. Database for Annotation, Visualization, and Integrated Discovery (DAVID) tools were used to interpret Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathways. Evaluation of the expression levels of CCT6A in COAD samples was also verified via immunohistochemistry. Key findings: We found that the expression of CCT6A is up-regulated in COAD. CCT6A correlated with poor prognosis and decreased immune infiltrates such as CD4+ T cells, B cells, and dendritic cells. CCT6A is increased in COAD patients. CCT6A is associated with several gene networks related to the DDX family and mismatch repair pathways. Significance: Our data showed that data mining was able to uncover data regarding levels of CCT6A and its involvement in genetic regulating pathways in COAD.